Aktivitas Nitrat Reduktase (ANR) Tanaman Jagung pada Pola Tumpangsari yang Diberi Serasah Jagung-Kedelai serta Biochar di Lahan Suboptimal Sidondo Sulawesi Tengah - Sjarfuddin Ende; Salawati Salawati; Indrianto Kadekoh; Fathurrahman Fathurrahman; Saiful Darman; Lukman Lukman (Jurnal Ilmu Pertanian Indonesia, 2022)
The aim of the study was to examine the relationship between nitrate reductase activity and N uptake, tissue N content, N uptake, and chlorophyll content of corn plants in intercropping patterns which are given corn-soybean litter and biochar. The use of plant litter and biochar derived from crop residues as a source of organic matter in different intercropping patterns affected nitrate reductase activity, tissue N content, N uptake, and chlorophyll content of maize. This experiment was carried out on sub-optimal Sidondo land, Central Sulawesi with the main limiting factors being the availability of water and alkaline soil pH (7.21) which were arranged in a divided plot design with five litter treatments as subplots and five cropping patterns as the main plot with three replicates. Parameters observed were N levels, plant tissue N uptake, chlorophyll, and nitrate reductase activity. Collected data were analyzed using Anova and Duncan's multiple random tests. The results showed that corn litter, soybean mixed corn + soybean litter and their biochar in different intercropping patterns affected nitrate reductase activity, nitrogen uptake, chlorophyll levels very significantly (P˂0.01), increased nitrate reductase activity by 9710.86 mol NO2- -1g-1hour-1 at the age of 55 DAP, while N uptake (2237 mg.kg-1), tissue N content (4.33%), and total chlorophyll content (10.61 mg.l-1) were the highest in the litter treatment, corn and soybeans as well as biochar in corn and soybean intercropping (1:2), and (2:4). Thus, the provision of corn and soybean litter and biochar in intercropping systems can increase nitrate reductase activity, N uptake, tissue N levels, and corn chlorophyll levels in the corn-soybean intercropping system. Keywords: chlorophyll, N content of corn plant tissue, nitrate reductase activity, N uptake